2010
DOI: 10.1186/1471-2407-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of brief psychological distress screening by a community-based telephone helpline for cancer patients and carers

Abstract: BackgroundUp to one-third of people affected by cancer experience ongoing psychological distress and would benefit from screening followed by an appropriate level of psychological intervention. This rarely occurs in routine clinical practice due to barriers such as lack of time and experience. This study investigated the feasibility of community-based telephone helpline operators screening callers affected by cancer for their level of distress using a brief screening tool (Distress Thermometer), and triaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 42 publications
(84 reference statements)
5
59
1
2
Order By: Relevance
“…The dt is a visual analog scale on which participants rate their level of distress in the preceding 7 days from 0 (none) to 10 (extreme). Some studies have suggested that a cut-off score of 4 or more indicates distress 35,36 ; others support a cutoff score of 5 or more 24 . The validity of the Chinese version of the dt was confirmed in a previous study 37 .…”
Section: Methodsmentioning
confidence: 99%
“…The dt is a visual analog scale on which participants rate their level of distress in the preceding 7 days from 0 (none) to 10 (extreme). Some studies have suggested that a cut-off score of 4 or more indicates distress 35,36 ; others support a cutoff score of 5 or more 24 . The validity of the Chinese version of the dt was confirmed in a previous study 37 .…”
Section: Methodsmentioning
confidence: 99%
“…A high dt score indicates severe distress. Some studies have determined that a cut-off score of 4 or greater indicates distress 40,41 . The validity of the Chinese version of the dt was confirmed in a previous study 42 .…”
Section: Methodsmentioning
confidence: 99%
“…A pesar de esto, la medicina en la actualidad al fraccionarse en diferentes especialidades va perdiendo su visión integradora, y en muchas de las ocasiones la paciente con cáncer de mama es manejada solamente desde el ámbito biológico, por lo que vive de manera personal su duelo, y utiliza sus propios recursos para llevar a cabo el afrontamiento (24,25) . Pocos son los países que tienen dentro de sus sistemas de salud un programa psicooncológico bien estructurado que le permita a estas pacientes tener una visión más adaptativa de su enfermedad (26,27) . A pesar de que las sociedades han cambiado, las investigaciones relacionadas con los factores psicosociales (28) y familiares (29,30) que influyen en la capacidad de afrontamiento y el incremento de la calidad de vida del paciente y su familia no se han actualizado (21,22) .…”
Section: Introductionunclassified